Development of a QR Code-based Woodworking Practice Jobsheet - Ramadhan, Raihan Ahlam; Prima, Fani Keprila (CIVED, 2024)
This research was motivated by the need for the development of jobsheets to support the learning process in the Wood Working Practices course at the Department of Civil Engineering, Faculty of Engineering, Padang State University. The purpose of this research is to produce a QR code-based jobsheet that is valid and practical to use as a learning support medium in the Wood Working Practices course. The research method used is Research and Development (R&D) with the DDD-E development model, which consists of Decide, Design, Develop, and Evaluate stages. The instrument used in this research is a questionnaire to test the validity and practicality of the product. The research subjects consisted of three lecturers or experts of the Wood Working Practices course who acted as assessors in the product validity level test, and 16 students of the Building Engineering Education study program who took the Wood Working Practices course in the July–December 2023 semester who played a role in the product practicality level test stage. The results of the validation test of the QR Code-assisted Wood Working Practice job sheet showed a high level of validity, with a rating of 94% for Media Expert 1, 92% for Media Expert 2, and 99% for Media Expert 3. As for the student usability test of the QR Code-assisted Wood Work Practice jobsheet, a score of 93% was achieved in the highly usable category. Based on the results of this study, it can be concluded that the QR Code-assisted Wood Work Practice jobsheet can be said to be valid and practical for use in the learning process of the Wood Work Practice course at the Department of Civil Engineering, Faculty of Engineering, Padang State University.